The Urgency of Professional Indemnity Insurance in Research and Innovation Practices in Indonesia - Permatasari, Yanti; Gultom, Elisatris; Hilmawan, Edi (Ridwan Institute, 2024)
Humans can never know the future because it is still covered by a veil of uncertainty. For this reason, humans must be prepared to face various bad things or risks that may occur in the future. In the wake of this development, an insurance system was implemented to protect individuals and businesses from unforeseen dangers and losses. Article 57 of the National System of Science and Technology Law places the position of Indonesian researchers as an important subject that deserves serious protection from the state. Article 57 of the National System of Science and Technology Law also reflects the state's recognition of the key role of researchers in the development of science and technology. The provisions of Article 57 of the National System of Science and Technology Law also impose an obligation on the Government as the owner of the Government authority to immediately formulate clear and comprehensive regulations to ensure adequate legal protection for researchers. The author formulates that to develop science and technology by providing adequate legal protection to researchers, supporting the realization of targeted development, and improving the welfare of society, the Government needs to immediately implement a policy in the form of enforcing professional insurance for researchers which is professional indemnity insurance.